2022
DOI: 10.1186/s12931-022-01977-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors impairing exercise capacity after severe COVID-19 pulmonary infection: a 3-month follow-up of prospective COVulnerability cohort

Abstract: Background Patient hospitalized for coronavirus disease 2019 (COVID-19) pulmonary infection can have sequelae such as impaired exercise capacity. We aimed to determine the frequency of long-term exercise capacity limitation in survivors of severe COVID-19 pulmonary infection and the factors associated with this limitation. Methods Patients with severe COVID-19 pulmonary infection were enrolled 3 months after hospital discharge in COVulnerability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 40 publications
3
24
0
4
Order By: Relevance
“…Impairment was predominantly related to persistent deconditioning or prior respiratory co-morbidities. These results confirm previous studies assessing exercise capacity by CPET 3 to 6 months after hospital release and reporting that remaining exercise limitation after COVID-19 is primarily related to physical deconditioning rather than to physiological impairment [5, 6, 17, 18]. Thus, recovery of physical capacities after a critical COVID-19 infection appears better than in patients with other ARDS etiologies [19, 20].…”
Section: Discussionsupporting
confidence: 88%
“…Impairment was predominantly related to persistent deconditioning or prior respiratory co-morbidities. These results confirm previous studies assessing exercise capacity by CPET 3 to 6 months after hospital release and reporting that remaining exercise limitation after COVID-19 is primarily related to physical deconditioning rather than to physiological impairment [5, 6, 17, 18]. Thus, recovery of physical capacities after a critical COVID-19 infection appears better than in patients with other ARDS etiologies [19, 20].…”
Section: Discussionsupporting
confidence: 88%
“…One other group previously demonstrated that hsCRP, IL-6, and TNF-α are associated with reduced peak VO 2 three months after COVID-19 hospitalization. 36 Our findings suggest that higher levels of SARS-CoV-2 antibodies and inflammation during the early post-acute period are associated with lower peak VO 2 more than a year later. Elevated inflammatory markers, especially hsCRP, IL-6, and TNF-α could be due to higher severity of acute illness, 37 persistent immune activation, 38 and/or ongoing antigen stimulation from viral persistence.…”
Section: Discussionmentioning
confidence: 53%
“…58 Consistent with our findings that elevated hsCRP is associated with reduced exercise capacity, one other group found that hsCRP, IL-6, and TNF-alpha are associated with reduced peak VO 2 3 months after hospitalization for COVID-19. 59 Elevated inflammatory markers are associated with reduced exercise capacity and chronotropic incompetence among adolescents and adults with obesity. 44, 60 In heart failure, resting heart rate is positively associated with levels of hsCRP, but chronotropic incompetence during exercise is negatively correlated with copeptin (C-terminal portion of arginine) and norepinephrine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical variability may result from the spectrum of LC severity and symptomatology. 37 Although some studies suggest that acute severity may not impact exercise capacity, 38,39 most studies suggest higher acuity is associated with worse exercise capacity. 31,36,40-42 One study reported worse peak VO 2 among unvaccinated compared to vaccinated individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Deconditioning was the most commonly identified pattern and the main cause of reduced exercise capacity reported by 8 studies. 39,40,42,46-51 Although ventilatory limitations were uncommon, multiple studies reported dysfunctional breathing or hyperventilation. 50,52-57 Muscular/peripheral oxygen extraction abnormalities were also commonly reported.…”
Section: Resultsmentioning
confidence: 99%